2021
DOI: 10.1007/s11192-021-03971-6
|View full text |Cite
|
Sign up to set email alerts
|

The sharing of research data facing the COVID-19 pandemic

Abstract: During the previous Ebola and Zika outbreaks, researchers shared their data, allowing many published epidemiological studies to be produced only from open research data, to speed up investigations and control of these infections. This study aims to evaluate the dissemination of the COVID-19 research data underlying scientific publications. Analysis of COVID-19 publications from December 1, 2019, to April 30, 2020, was conducted through the PubMed Central repository to evaluate the research data available throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 41 publications
(47 reference statements)
2
29
0
Order By: Relevance
“…They searched PubMed Central and found underlying research data available for only 13.6% of the analyzed records. They concluded that data sharing was not a common practice, even in health emergencies, such as the beginning of the COVID-19 pandemic (Lucas-Dominguez et al, 2021 ). However, such analysis of data availability is not available for preprint articles.…”
Section: Introductionmentioning
confidence: 99%
“…They searched PubMed Central and found underlying research data available for only 13.6% of the analyzed records. They concluded that data sharing was not a common practice, even in health emergencies, such as the beginning of the COVID-19 pandemic (Lucas-Dominguez et al, 2021 ). However, such analysis of data availability is not available for preprint articles.…”
Section: Introductionmentioning
confidence: 99%
“…The debate about who hosts and curates datasets is especially relevant when it comes to responsibility for privacy, legal, and ethical issues related to supplementary materials. This explains, for example, how even in publications related to the COVID-19 pandemic, there have been low levels of data sharing [31]. A similar explanation would also make sense in relation to the criterion on self-citations.…”
Section: Resultsmentioning
confidence: 92%
“…1 However, barriers for data users and data stewards persist in our very connected global community. 2 A significant challenge to accelerating genomics-based research is the ability of organizations to manage data access processes and verify user identity and permissions. For data users, discovering and gathering sufficient data to address a hypothesis and then gaining data access approval can be time consuming.…”
Section: Introductionmentioning
confidence: 99%